Implementasi Internet of Things (IoT) dalam Memonitoring Komsumsi Listrik - Dedi Suarna; Edy Sopyan Edy (Bulletin of Information Technology (BIT), 2023)
Electricity is one of the main needs that supports people in their activities, starting from studying, working, and even enjoying entertainment through electronic devices that use electricity. However, the use of electricity that is not turned on can result in wastage of electricity. One of the Regional Apparatus Organizations that has a large electricity consumption, namely the General Bureau of the Regional Secretariat of West Sulawesi Province, can be seen from the number of electricity bills paid each month. This study aims to monitor and control electricity consumption to minimize excessive use of electrical energy by utilizing microcontrollers and sensors. The research was carried out by testing stages in three work rooms, namely the personnel room, the mail room and the Urdal room. Electronic equipment that is monitored and controlled such as lights that are connected to an electric current (socket) on the designed device. The result is a range of 110 dejar pear motion sensors and a maximum range of 7 meters requiring a minimum of 2 sensors for each room and saving the energy consumption of electrical equipment in three rooms by 49%. The conclusion of this research is that the system is designed to provide a good path in saving the consumption of electronic equipment..